Control of Population Growth and Quality Family in Denpasar City - Pujawati, Desak Putu (Journal of A Sustainable Global South; Vol 8 No 2 (2024): August 2024, 2024)
Family Quality is caused by growth (birthrate, mortality and migration) as well as optimizing family function like parenting; development training for children, teenager and elderly; and decreasing number of modern contraceptives. Denpasar City Goverment has made policy to increase family quality by make a workplan document based on analisys of results and evaluation of targets list in 2021-2026 name The Annual Workplan and Strategic Plan Document consisting of 10 programs, 25 sub activities and 58 sub activities. Performa achievement of the government is determined by 3 targets and 4 main indicators like Child-Friendly City, Gender Development Index, Gender Empowerment Index, and Family Development Index. The policy paper is writed by collecting and data processing methode, which by interview, focus group discussion and literature study method. The data is analized by combine quantitative analisys using various instrument in preparation and implementation stage at the Government Work Plan Document dan Woment’s Empowerment Service Work Plan Document like RKPD, Strategic Planning Document, Goverments Performance Report, Cause and Effect Analysis using logical framework and work table. This thecnique are use to identify the relation of the document.